Influence of polypropylene fiber with Styrene-Butadiene Rubber Latex bonding agent in prevention of early crack of concrete - Ali, Shaik Shahid; Kunte, Anil; Roy, Aashis (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
We have fabricated the concrete reinforced polypropylene fiber with styrene-butadiene rubber latex bonding agent of concrete in different ratio. The prepared concrete employed with structural studies using FTIR and XRD spectra. An FTIR spectrum shows the important characteristics peaks of polypropylene fiber and styrene-butadiene rubber along with silica peaks. XRD pattern indicates that concrete crystal structure of three polymorphs such orthorhombic, triclinic and monoclinic phase. SEM image indicates that the above 10 wt % of polypropylene fiber causes small hairline cracks on its surface. It is found that the tensile strength increases with increase in different weight percentage of polypropylene fiber up to 10 wt %. This is may be due to the high compactness and reduction in porosity of the concrete block. It is also important to note that the water reduce admixture such as Polycarboxylates in required ratio’s significantly effects on capillary threshold by reducing 8-12 % of water results higher density of the concrete.